(untitled) (Third Sector Social Economic Review, 2024)
This research aims to examine the effect of servant leadership on work engagement. The main goal of this study is to understand the effects of leadership styles on work engagement and to identify strategies and draw conclusions to create a more positive work environment. Data were collected from education sector employees through questionnaires. The SmartPLS program was used for data analysis in the research. Correlation analysis was utilized to explain the relationship between variables, and cross-factor loadings were examined to confirm Discriminant Validity. Additionally, Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis and the method of least squares were employed for structural equation modeling. Our analyses demonstrate that servant leadership positively affects the sub-dimensions of work engagement i.e. vigor, dedication, and absorption. From this point of view, it has been revealed how the servant leadership style affects the workplace dynamics and how this leadership style is an important element in creating a motivating work environment.